Religion as Legitimacy and Hypocrisy: Analysis of the Drama Series Bidaah - Annisa Rahmalia Dardiri (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
Bidaah is a Malaysian drama series released on March 6, 2025, and aired on the VIU and Trans TV Indonesia platforms since June 2, 2025. In short, this drama series tells the story of Islamic religious practices taught by religious leaders, but considered unnatural and deviant because they use religious doctrine to legitimize personal interests. This study uses Tzevetan Torodov's analysis theory and Michel Foucault's theory of power. Tzevetan Torodov's theory is used to explain the plot of the drama series in a structured manner and to reveal the elements of religious legitimacy and hypocrisy in it. Michel Foucault's theory of power is used to explain the existence of knowledge that goes hand in hand with power, which unconsciously gives rise to certain understandings. This study uses a qualitative approach by conducting a digital study as the primary data source. In addition, secondary data sources are also needed in the form of books and journals with relevant themes as supporting references. The results of this study show that religion as a form of legitimacy and hypocrisy is depicted in the drama series Bidaah in the form of religious teachings that are used to fulfill personal interests.